Effect of Social Media Sentiments on Investment Decisions and Risk Perception: Evidence from the Pakistan Stock Exchange - Muhammad Suliman; Uzair Khan; Afzal Khan (Indus Journal of Social Sciences, 2025)
The purpose of this study is to study the impact of social media platforms, particularly Facebook and LinkedIn, on investment decision of investors at the Pakistan Stock Exchange (PSX). The results show a strong and positive link between the use of social networks and adoption of investment decisions. Correlation and regression analyses show that social media platform have a significant impact on investor choice, shape access to information, and recognize risky relationships with market trends. Investors are increasingly counting on these platforms, gathering understandings about the effectiveness of actions, sharing ideas, and training expectations. The results also confirm that risk perception plays a softening role in the relationship between social networks and investment decisions. Social networks provide timely information, but can also improve behavioral bias and lead to decision-making. Therefore, this study contributes to the increase structure of literature in behavioral finance, highlighting the role of social networks as opportunities and tasks for investors. The results highlight that social networks are no longer peripheral tools, but are central factors that influence PSX investors’ decisions or behaviors. However, it expands access to market information, but expands excessive dependencies without an appropriate assessment of trust and risk, allowing investors to reveal disinformation, volatility and irrational behaviors in the pack.